TrkA mediates developmental sympathetic neuron survival in vivo by silencing an ongoing p75NTR-mediated death signal - Majdan, Marta (The Rockefeller University Press, 2001)
Developmental sympathetic neuron death is determined by functional interactions between the TrkA/NGF receptor and the p75 neurotrophin receptor (p75NTR). A key question is whether p75NTR promotes apoptosis by directly inhibiting or modulating TrkA activity, or by stimulating cell death independently of TrkA. Here we provide evidence for the latter model. Specifically, experiments presented here demonstrate that the presence or absence of p75NTR does not alter Trk activity or NGF- and NT-3–mediated downstream survival signaling in primary neurons. Crosses of p75NTR(−/−) and TrkA(−/−) mice indicate that the coincident absence of p75NTR substantially rescues TrkA(−/−) sympathetic neurons from developmental death in vivo. Thus, p75NTR induces death regardless of the presence or absence of TrkA expression. These data therefore support a model where developing sympathetic neurons are “destined to die” by an ongoing p75NTR-mediated apoptotic signal, and one of the major ways that TrkA promotes neuronal survival is by silencing this ongoing death signal.